Mechanism of Viral Glycoprotein Targeting by Membrane-Associated RING-CH Proteins - Cheng Man Lun (American Society for Microbiology, 2021)
Viral envelope glycoproteins are an important structural component on the surfaces of enveloped viruses that direct virus binding and entry and also serve as targets for the host adaptive immune response. In this study, we investigate the mechanism of action of the MARCH family of cellular proteins that disrupt the trafficking and virion incorporation of viral glycoproteins across several virus families.